Association between duration of the sleep and body weight - Adámková, V; Hubáček, J A; Lánská, V; Vrablík, M; Králová Lesná, I; Suchánek, P; Zimmelová, P; Veleminský, M (Physiological research, 2009)
Some studies have suggested that there could be an association between the duration of sleep in humans and development of the obesity. We have analyzed the group of the probands (n = 3970, 2038 males and 1932 females, aged 18-65 years), with permanent address in the Central or South Bohemia. We ascertained the relationship between the duration of their sleep (obtained per questionnaire) and body mass index, weight, height, the value of systolic and diastolic blood pressure, heart rate, waist and hip circumference, the values of total-, high density- and low density- cholesterol, thyroid hormone and body exercise performed. The optimal values of the body mass index (and optimal body weight) were associated with the duration of sleep 7 hours per night (P < 0.001). This association was found both in males and females and in both districts. Other anthropometrical and biochemical parameters were not associated with the sleep duration.
Keywords: Young Adult; Sleep Deprivation; Male; biologické markery; Thyroid Hormones; Obesity; spánková deprivace; Risk Factors; mladý dospělý; Biomarkers; hormony štítné žlázy; Adolescent; Heart Rate; obezita; Adult; Body Height; Aged; dospělí; mužské pohlaví; senioři; tělesná výška; srdeční frekvence; průzkumy a dotazníky; Body Weight; mladiství; Waist Circumference; Sleep; Time Factors; lipidy; lidé; krevní tlak; ženské pohlaví; Humans; Body Mass Index; spánek; časové faktory; rizikové faktory; Blood Pressure; obvod pasu; index tělesné hmotnosti; Lipids; Female; Surveys and Questionnaires; lidé středního věku; tělesná hmotnost; Middle Aged